Nonadditive and allele-specific expression of ghrelin in hybrid tilapia - Zhong, Huan; Ren, Bingxin; Lou, Chenyi; Zhou, Yi; Luo, Yongju; Xiao, Jun (Frontiers in Endocrinology, 2023)
Background: Interspecies hybridization is an important breeding method to generate fishes with heterosis in aquaculture. Using this method, hybrid Nile tilapia (Oreochromis niloticus, ♀) × blue tilapia (Oreochromis aureus, ♂) has been produced and widely farmed due to its growth and appetite superiorities. However, the genetic mechanism of these advanced traits is still not well understood.Ghrelin is a crucial gene that regulates growth and appetite in fishes. In the present study, we focused on the expression characteristics and its regulation of ghrelin in the hybrid.The tissues distribution analysis showed that ghrelin predominately expressed in stomach in the hybrid. Ghrelin was higher expressed in stomach in the hybrid and Nile tilapia compared to blue tilapia showing a nonadditive pattern. Two single-nucleotide polymorphism (SNP) sites were identified including T/C and C/G from the second exon in ghrelin gene from N and B. By pyrosequencing based on the SNP sties, the allele specific expression (ASE) of ghrelin in the hybrid was assayed. The result indicated that ghrelin in the hybrid showed higher maternal allelic transcript ratios. Fasting significantly increased ghrelin overall expression at 4, 8, 12, 24 and 48 h. In addition, higher maternal allelic transcript ratios were not changed in the fasting hybrids 48 h. The cis-and trans-effects were determined by evaluating the overall expression and ASE values in the hybrid. The expression of ghrelin was meditated by compensating cis-and trans-effects in hybrid.In summary, the present evidences showed the nonadditive expression of ghrelin in the hybrid tilapia and its regulation by subgenomes, offering new insight into gene expression characteristics in hybrids.